Computational Architecture of Digital Waqf in Indonesia - Fatimah Zahara; Bambang Sugiharto; Yenni Samri Juliati Nasution (Jurnal Penelitian Pendidikan IPA, 2024)
It is a necessity that information technology with the power of digitalisation is experiencing accelerated development. Its application also penetrates into various fields. On the other hand, the potential of cash waqf in Indonesia is also very large. The purpose of this paper is to describe the potential of cash waqf developed through digital mechanisms, by utilizing computing technology. The institutionalization of the spirit of digital-based waqf is the focus of attention in this study. The method used is descriptive qualitative with a literature review approach. The data taken are secondary data derived from scientific journals, academic papers, books that are compatible with this study. Digital artifacts of digital waqf institution platforms are also a relevant and main source of study in this discourse. The study found that the development and transformation of digital cash waqf began in 2012 when the Indonesian Ulema Council issued a fatwa on cash waqf. The study also found that cash waqf began to grow in the community and was amplified by the presence of digital instruments in the implementation of cash waqf payments. Many waqf institutions build digital platforms through various applications, websites and other social media.